Goldstone [videorecording (DVD)] - Sen, Ivan; Sen, Ivan; Pedersen, Aaron, 1970-; Russell, Alex, 1987-; Weaver, Jacki, 1947- (Lightyear Entertainment, 2018)
Searching for a missing person, a detective arrives in the mining town of Goldstone and discovers a web of corruption, conspiracy, human trafficking and other crimes.